Prosodic variation in european portuguese:phrasing, intonation and rhythm in central-southern varieties - Cruz, Marisa (2014)
Tese de doutoramento, Linguística (Linguística Portuguesa), Universidade de Lisboa, Faculdade de Letras, 2013